Sacred and secular: A plea to re-examine the worldview among Myanmar Christians - Sang Thein Thang (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2022)
The Myanmar Christian worldview on sacred and secular is the product of primarily two basic grounds; the Burmanization and Myanmar Christian understanding on Church and State, which eventually lead subjugation of the Church to political authority of the Burman government. As a result, it leads one to seeing political and social actions as secular, and Christians therefore need to be restrained from that sort of things. But anything is secular or sacred depending on the direction being used towards: in obedience or disobedience towards God??"s law and order. The Church as community of God??"s people has responsibility as a voice and witness of God for restoring God??"s standards of life aspects; culture, social activities, politics, business, education, and so on in the fallen community and society.